‘Crime before it happens’: new technologies, old promises - Gatti, Carlo (University of Turku, 2026)
Predictive Policing is a buzzword gaining increasing attention both within and beyond academia. However, as is often the case when socio-technical phenomena are wrapped in clichéd tropes for communicative immediacy, utopian or apocalyptic fantasies cloud efforts to understand the implications of predictive algorithms in policing.